Hydrogen saline water accelerates fracture healing by suppressing autophagy in ovariectomized rats - Guo, Jialiang; Tian, Siyu; Wang, Zhongzheng; Wang, Yuchuan; Zhang, Xiaojuan; Zhang, Yingze; Hou, Zhiyong; Dong, Weichong (Frontiers in Endocrinology, 2022)
Abstract Objective: The treatment of osteoporotic fractures is difficult, and to minimize the negative result or poor functional rehabilitation, this research focuses on hydrogen water (HRW) to test its effect on the process of menopausal osteoporotic fracture healing and its relationship with autophagy and to try to reveal the potential mechanism of action of HRW on osteoporotic fractures. Materials and methods: An osteoporotic fracture was established, and HRW was systematically applied with or without 3MA. The results were analyzed with X-rays, micro-CT scans, serum biomarker analysis, biomechanical tests, histopathology, immunohistochemistry, and Western blot assays. The sham, OVX, OH (OVX+HRW) and OHA (OVX+HRW+3MA) groups were formed and compared. Results: Increased oxidative stress and autophagy levels were necessary physiological responses in the process of fracture healing. It was found that systemic HRW treatment slightly suppressed autophagy and then activated the Keap1-Nrf2 system by enforcing the Keap1-Nrf2-p62 interaction and improved the osteoporotic fracture healing process. Conclusion: HRW treatment activated Nrf2-Keap1 pathways to antagonize cellular stress by suppressing autophagy levels, especially at the early stage of the fracture healing process, and it was beneficial to osteoporotic fracture healing in rats.